Impaction bone grafting for acetabular bone defects replacement in revision hip arthroplasty: biomechanical aspects - Golnik, Vadim N.; Fedorova, Natalia V.; Larichkin, Alexey Y.; Boyko, Svetlana V.; Panchenko, Andrey A.; Kosinov, Alexandr M.; Peleganchuk, Vladimir A.; Pavlov, Vitaliy V. (Travmatologii͡a︡ i ortopedii͡a︡ Rossii, 2024)
Background. The leading role in long-term survival of the prosthesis installed using impaction bone grafting is given to the mechanical properties of the graft. The aim of the study is to explore the mechanical properties of osteoplastic material and determine the potential impact of cyclic loads on dynamic changes in the position of the acetabular component after revision hip arthroplasty using impaction bone grafting. Methods. We conducted an experiment evaluating the impact of cyclic loads on the mechanical properties of osteoplastic material. At the first stage, a single-cycle tension-compression testing was carried out. Cyclic tests were carried out at the second stage of the experiment. Taking into account the presence of blood in the wound, we provided for a model with an aqueous solution of 45% glycerin. Clinical interpretation of biomechanics was carried out basing on the dynamic radiography data of two patients who underwent revision hip arthroplasty with the use of impaction bone grafting (IBG). The changes in the position of the rotation center and acetabular component were assessed. Results. During a single-cycle loading, we observed stress-strain dependences and instantaneous elastic moduli for each specimen. During cyclic tests, we obtained the increase of the instantaneous elastic modulus by 2.6 times for a “dry” specimen and from 3.9 to 4.7 times for the ones with liquid. X-rays of both patients showed the shift of the center rotation cranially and laterally: 2.4 and 1.5 mm in the first case and 14.9 and 9.5 mm in the second one, respectively. In the first case the change in the inclination was 18.7º, in the second case — 19.8º. The Hip Harris Score (HHS) was 97 points for the first patient, 53 points — for the second one. Conclusions. The material used for IBG is subject to deformation both in the intraoperative and postoperative period. Compression tests have suggested that the deformation of morselized impacted bone graft gradually tends to reach a plateau in the postoperative period, and with the completion of the deformation, migration of the acetabular component stops. The change in the position of the rotation center and acetabular component in the absence of a radiolucent line is not an absolute sign of loosening.